Kant e o mal: a impossibilidade de uma vontade diabólica na natureza humana - Santos, Cláudio Ananias Alves dos (2018)
The theme of evil in Kantian philosophy stems from its approach to morality whose concept of evil, in short, is to go against the moral law, although evil is in the performance of an action that is not a moral action, since the moral law to achieve the highest possible good through us. Kant objectively approaches evil in his work, Religion within the Boundaries of bare Reason, 1793, and for this he presents it on three levels: the evil of weakness, the evil of impurity and malignity. However, it indicates the concept of a fourth level that would not be possible, namely a diabolical will. Weakness would be a penchant for an action that goes against our own maxims, being weak and acting inversely to the moral law. The impurity is in a correct action that, however, is not based on the moral law. Malice would be the decision to do evil, having selfish motives and intentions in front of the moral law. But the fourth level of evil, which for Kant would not be possible to exist, consists in a malign action in which a purely devilish will is established. Evil in this sense, diabolical, proposes its desire from a natural corruption of the will. Kant presents this concept, but understands that it is not possible, since human actions of this kind of evil would be justified in reason itself, since such evil would be the disposition of spirit admitting as a motive evil as evil in its own maxim. Since Kant understands that man does not attain to the condition of a diabolic will, the present research seeks to investigate why in Kant the diabolical evil (in the sense of innate inhumanity or a natural pleasure in evil) would not be possible. Starting from the key concepts that discusses morality in Kant, such as freedom, categorical imperative, will, intention, good and evil, we intend to analyze the impossibility of this pure evil in human nature.